REPRESENTASI SIKAP MANUSIA MELALUI FOTOGRAFI POTRET - Ine Rachmawati (Saraswati)
Humans have a diverse attitude to face everyday life. Attitudes that emerge due to both positive and negative reciprocal response between people. Action can only be felt and seen with hearts and can not be shaped as an object or form of a figure. It become an idea in visualizing the action of attitude in the creation of artwork. Portrait photography in the creation of this artwork is a visual medium to express ideas. An idea were visualized in metaphor as a form of representation of human attitude. The process of creating artwork using techniques of portrait photographs as suppression of identity. This identity is shown through the background, facial expression, and properties used. Portrait photography in this artwork is not only a portrait of identity, but also become a visual medium in expressing an idea in a sign visualize through metaphor. Keywords: representation, gesture, human, portrait photography.∗Korespondensi